دور أخوان الصفا فى الفكر الجغرافى العربى الإسلامى فى مجال الجغرافية الطبيعية - الخشمان، سحر عادل غضب عجيل Alkhashman, Sahar Adel Ghadab Ajil; العبيدى، محمد عباس حسن (تكريت, 2011)
Ikhwanussafa are a group emerged in Basra in mid 4th century A. H. ( 10th A. D. ) i. e. in the era of prosperity of education and ideology which is called " The golden era " of scientific research . The name " Ikhwanussafa is derived from the word " Safa " which means the hard stone. While "Ikhwan" means brothers . It is not clear how the connection came but it suggests a relation with some of the components of nature. Ikhwanussafa gave the science of geography a lot of their interest . They wrote 52 letters . Those letters were wrote in a loose manner and not in a firm methodology . Their ideas were scatterent here and there with repetition and mixing between different sciences of philosophy, mathematics , nature, magic, astrology, literature, geography and history. Their writings were an encyclopedia containing all kids of sciences in that era. They followed the scientific methods of research ; inductive, deductive and measurement. They wrote in the field or natural geography more than in human geography . The researcher chose to write about them to highlight the Arab-Islamic geographical heritage in addition to the fewness of writings about this group. The aim of this thesis is to show their participations in natural geography and their scientific additions espscially in the four branches of geomorphology, climate, hydrology and astronomy. The purposes of the research are two; love to our scientific heritage and the need to produce this heritage in a scientific way . The thesis is divided into four chapters as follows : 1. Chapter One dealt with the theoretical frame in addition to the introduction . 2. Chapter Two is under the title of development of geography by the Arabs. It contained four sections ; geography evolving by Arabs, stages of developing of the geographical – ideology, factors of developing of geography and properties of Arab-Islamic geographical ideology . 3. Chapter Three is titled : Ikhwanussafa and their scientific method . It contains three sections ; their life , method of writing they followed and their scientific research method . 4. Chapter Four is about the role of Ikhwanussafa in natural geography . It contains four sections ; climate , geomorphology , hydrology and astronomy . Deductions : 1. Ikhwanussafa were not mere conveyers of geographic concepts from former nations , the Greeks and the Romans, but they put a great effort in investigating their books correcting their mistakes adding a lot to them to provide them in front of the scholars in a scientific method. 2. Ikhwanussafa relied in their letters on their observation and investigation through their travels that reached many countries . That made their letters original and reliable . 3. The ideas of Ikhwanussafa in the fields they studied were very near to modern scientific interpretations. 4. Ikwanussafa participated in developing the theoretical side of geomorphology while in regional geography they reviewed the existing cities in their time and the habits and traditions of their . They also laid the foundations of climate and the information of Quran . In hydrology they provided valuable information about groundwater. 5. They made a great effort in astronomy laying many theories, calculated the size and area of earth, the seasons of the year and discovered many facts the sphericity of Earth . Recommendations : 1. It is necessary to insist on the pioneer role of Arabs in geography as some are trying to suppress facts about the first Arab geographers . 2. Iraqi univeraities should safeguard the heritage of our ancestor through participating in developing the theoretical studies . 3. Holding academic conferences and symposiums to clarify the role of the Arab scientists in various sciences and urging students to attend them . 4. Insisting on the role of the Arab geographers in various branches of geography in laying theorise and bases of scientific geography . 5. Reprinting and issuing the books of Arab and Muslim geographers to make them available for all those who need them in the field of scientific research .
Keywords: الجغرافية الطبيعية -- الفكر الإسلامي -- العالم العربي -- إخوان الصفا -- الفلسفة الإسلامية